Cognitive correlates of cerebrospinal fluid biomarkers in frontotemporal dementia. Issue 3 (30th July 2012) - Koedam, Esther L.G.E.; van der Vlies, Annelies E.; van der Flier, Wiesje M.; Verwey, Nicolaas A.; Koene, Ted; Scheltens, Philip; Blankenstein, Marinus A.; Pijnenburg, Yolande A.L.
Abstract: Objective: In this study we investigated the relationships between cerebrospinal fluid (CSF) biomarkers (tau and amyloid‐β1‐42 [Aβ1‐42 ]) and cognition or behavior in patients with frontotemporal dementia (the behavioral variant, bvFTD). Methods: We included 58 patients with bvFTD. All patients underwent a neuropsychological assessment and lumbar puncture. Relationships between CSF biomarkers and cognition or behavior were assessed with linear regression analysis. Results: After correction for age, sex, and education, CSF tau levels were found to be negatively related to the Visual Association Test (standardized β = −0.3, P < .05), whereas CSF Aβ1‐42 levels were found to be positively related to the Mini‐Mental State Examination (β = 0.3, P < .05), the frontal assessment battery (β = 0.5, P < .05), and digit span backwards test (β = 0.3, P = .01). We did not find relations between CSF biomarkers and behavior (measured by the neuropsychiatric inventory). After excluding all patients with a CSF biomarker profile often seen in Alzheimer's disease (high levels of tau and low levels of Aβ1‐42 ), we still found relations between CSF Aβ1‐42 levels and Visual Association Test object naming (β = 0.4, P < .05), as well as between CSF Aβ1‐42 levels and the frontal assessment battery (β = 0.5, P < .05, but there was no relation between CSF tau and cognition. Conclusion: Low CSF Aβ1‐42 levels are associated with worse general cognitive function and worse executive function in patients with bvFTD. Our results provide circumstantial evidence for a pathophysiological role of Aβ1‐42 in bvFTD.